Amino acid-assisted synthesis of In2S3 hierarchical architectures for selective oxidation of aromatic alcohols to aromatic aldehydes. Issue 11 (19th January 2017) - Li, Tongtong; Zhang, Sujuan; Meng, Sugang; Ye, Xiangju; Fu, Xianliang; Chen, Shifu
Abstract : Flowerlike-In2 S3 photocatalyst was prepared via a biosynthesis technique and showed high activity toward the selective oxidation of aromatic alcohols. Abstract : In this work, we report a facile and bioinspired synthesis of mesoporous indium sulfide nanoparticles with flowerlike structures controlled by amino acids. During the synthesis procedure, indium sulfide precipitate was prepared by a simple solvothermal method with different amino acids as the directing and assembling agent. The resulting photocatalyst was characterized by X-ray powder diffraction (XRD), scanning electron microscopy (SEM), UV-vis diffuse reflection spectroscopy (DRS), transmission electron microscopy (TEM), Brunauer–Emmett–Teller (BET) specific surface area, electron spin resonance (ESR) and X-ray photoelectron spectroscopy (XPS). Depending on different amino acids as the crystallization modifiers, the indium sulfide samples exhibit different morphologies. The photocatalytic test of selective oxidation of aromatic alcohols to aromatic aldehydes under visible light irradiation shows that indium sulfide nanoparticles synthesized with addition of amino acids exhibit an increased photoactivity compared to that of In2 S3 nanocatalyst without amino acids, which can be attributed to both the relatively high BET surface area and effective separation of photogenerated charge carriers. The effect of various radical scavengers is also investigated. ˙O2 − radicals and holes are the main reactive species for photocatalytic oxidation of benzyl alcohol (BA) to benzaldehyde (BAD).